‘No Strings Attached’: Welcoming the Existential Gift in Business - Frémeaux, Sandrine; Michelson, Grant (2011)
Social relations are predominantly influenced by an exchange paradigm whereby the logic of reciprocity shapes behaviour. If the notion of exchange instrumentalism is common across different business disciplines, this does not deny attempts – such as through gift exchange theory – to present different conceptions of traditional exchange-based relations. Gift exchange theory appears promising as it seeks to establish more meaning and significance to the nature and context of exchange relations between human actors or parties. The underlying processes may be different for gift exchange and more traditional economic-based exchanges, but the general outcome remains the same – the obligation of reciprocity between actors. In this article, we develop an alternative conception of social and business experience that transcends the dominant logic of exchange: the existential gift. Firmly embedded in the idea of giving for its own sake, the existential gift suggests that for some individuals the expectations of reciprocity are neither sought nor established. Generosity that is expressed in both tangible and intangible ways need not depend on the response of intended receivers or recipients (e.g. acceptance or non-acceptance) to precipitate future acts of giving. Based on the logic of unconditionality, the existential gift provides human actors with greater freedom in their choices and relationships. It may well be that this freedom, in turn, creates a new ‘ethic of generosity’ whereby significant progress can be made towards developing more human models and practices in business.
Keywords: Gratuitousness; existential gift; Reciprocity; gift exchange; Social Relations